The Effect of Service Quality through the Patients Satisfaction to Word of Mouth at Praktik Mandiri Bidan Maria Surabaya - Ulul Abror; I Nyoman Sudapet; Hamzah Denny Subagyo; Joko Suyono (Yayasan Ahmar Cendekia Indonesia, 2021)
The aim of this study: (1) to analyze the effect of service quality on Patient Satisfaction, (2) to analyze the effect of service quality on Word of Mouth, (3) to analyze patient satisfaction with Word of Mouth. This research is quantitative research. Population and sample distributed were 252 respondents. Data collection techniques using a questionnaire. Analysis of the data used is Convergent Validity, Discriminant Validity, Reliability and Average Variance Extracted (AVE). The results showed that the effect of the Service Quality variable (X1) on patient satisfaction (Y1) was significant at 0,000 and Service Quality (X1) is significant with variable Word of Mouth (Y2) of 0.002 which means medium. Based on the correlation for the Patient Satisfaction variable (Y1) for Word Of Mouth (Y2) of 0,000 which means strong. The results of this study indicate that, quality of service, has a significant influence on patient satisfaction, which leads to word of mouth patients. While patient satisfaction has no significant effect on Word of mouth patients.